An Innovative Inhibitor with a New Chemical Moiety Aimed at Biliverdin IXβ Reductase for Thrombocytopenia and Resilient against Cellular Degradation - Hoe-Myung Jung; Jung-Hye Ha; Mark Vincent C. dela Cerna; Joseph A. Burlison; Joonhyeok Choi; Bo-Ram Kim; Jeong Kyu Bang; Kyoung-Seok Ryu; Donghan Lee (Pharmaceutics)
Biliverdin IXβ reductase (BLVRB) has emerged as a promising therapeutic target for thrombocytopenia due to its involvement in reactive oxygen species (ROS) mechanisms. During the pursuit of inhibitors targeting BLVRB, olsalazine (OSA) became apparent as one of the most potent candidates. However, the direct application of OSA as a BLVRB inhibitor faces challenges, as it is prone to degradation into 5-aminosalicylic acid through cleavage of the diazenyl bond by abundant azoreductase (AzoR) enzymes in gut microbiota and eukaryotic cells. To overcome this obstacle, we devised olsalkene (OSK), an inhibitor where the diazenyl bond in OSA has been substituted with an alkene bond. OSK not only matches the efficacy of OSA but also demonstrates improved stability against degradation by AzoR, presenting a promising solution to this limitation. Furthermore, we have found that both OSK and OSA inhibit BLVRB, regardless of the presence of nicotinamide adenine dinucleotide phosphate, unlike other known inhibitors. This discovery opens new avenues for investigating the roles of BLVRB in blood disorders, including thrombocytopenia.